Gene expression analysis of heat-shock proteins and redox regulators reveals combinatorial prognostic markers in carcinomas of the gastrointestinal tract - Pohl, S.Ö.-G. (Elsevier B.V., 2021)
10.1016/j.redox.2018.11.018